Anticancer Effects of Amlodipine Alone or in Combination With Gefitinib in Non-Small Cell Lung Cancer - Fu, Bingjie; Dou, Xiaojing; Zou, Miao; Lu, Hao; Wang, Kaixuan; Liu, Qingxia; Liu, Yao; Wang, Wei; Jin, Meihua; Kong, Dexin (Frontiers in Pharmacology, 2022)
Amlodipine is a Ca2+ channel blocker commonly used to cardiovascular diseases such as hypertension and angina; however, its anticancer effects in lung cancer A549 cells remain unknown. In the present study, we explored the antitumor effects and molecular mechanisms underlying the action of amlodipine in non-small cell lung cancer (NSCLC) A549 cells in vitro and in vivo. We observed that amlodipine suppressed the proliferation of A549 lung cancer cells by arresting the tumor cell cycle. Mechanistically, our results revealed that amlodipine could attenuate the phosphoinositide 3 kinase (PI3K)/Akt and Raf/MEK/extracellular signal-regulated kinase (ERK) pathways through epidermal growth factor receptor (EGFR) and modulated cell cycle-related proteins such as cyclin D1, p-Rb, p27, and p21. Subsequently, amlodipine combined with gefitinib could synergistically inhibit cell proliferation by arresting the cell cycle. Moreover, amlodipine combined with gefitinib effectively attenuated the growth of A549 lung cancer xenografts when compared with monotherapy, affording an excellent therapeutic effect. Collectively, our results indicate that amlodipine alone or combined with the novel anticancer drug gefitinib might be a potential therapeutic strategy for NSCLC patients with wild-type EGFR.